Peran Lembaga Pemberdayaan Masyarakat (LPM) dalam Pembangunan Desa (Studi Kasus di Desa Sabalana Kecamatan Liukang Tangaya Kabupaten Pangkep) - Fatimah Aziz; Irmawati Irmawati (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2021)
The Role of Community Empowerment Institutions in Village Development in Sabalana Village, Liukang Tangaya District, Pangkep Regency. Educational Sciences, Muhammadiyah University of Makassar. This study aims to determine the role of Community Empowerment Institutions in Village Development, the supporting and inhibiting factors of Community Empowerment Institutions in Village Development. This study used descriptive qualitative research. In this study, the informants were selected directly by the researcher who was called the research target. Based on the characteristics, the informants who had been appointed were the Village Head, Head of the Community Empowerment Institute and the Villagers. This study used observation and interviewing as a tool to collect the data. Based on the results of research in the field, the researcher could see that the role of the Community Empowerment Institution in Village Development in Sabalana Village where the chairman and members of the Community Empowerment Institute have carried out their duties and functions in carrying out every development carried out in Sabalana Village but has not been very effective yet. Factors that support Community Empowerment Institutions in Village Development are the resources owned by the Village officers and always holding coordination meetings. The inhibiting factors of the Community Empowerment Institution in Village Development are sea transportation and the lack of participation of the Villagers in assisting the village officers and the head of the Community Empowerment Institute in carrying out any existing development. The success of the Community Empowerment Institution in increasing development in Sabalana Village, therefore, there is a need for cooperation between the village officers, head of the Community Empowerment Institution (LPM) and the villagers.